Ghost in the guacamole [large type] - Jaffarian, Sue Ann, 1952- (Jaffarian, Sue Ann, 1952- Ghost of Granny Apples mystery., 2015)
Sisters Lucinda and Ricarda Ricardo are at each other's throats over the family business. Lucy wants to sell and Rikki doesn't. Rikki asks medium Emma Whitecastle to contact their deceased father for help. But the ghost of Felix Ricardo drops a bombshell -- his death was not an accident, and Rikki's life may be in danger if the girls don't sell.